An empirical study of the concepts process of manufacture and similar process - F. J. Mostert (South African Journal of Business Management, 1987)
The concepts process of manufacture and similar process are very important to manufacturing enterprises as new or unused machinery and plant must be employed in one of the two processes to qualify for a 50% initial allowance. On the other hand only buildings or improvements thereto are in line for an Investment or initial allowance if the assets are used in a process of manufacture. An empirical study of the two concepts concerned revealed that a process of manufacture or similar process is clear to the majority of responding companies. Allegations made by a number of companies concerning the two concepts do not have much substance, but the concept of process of manufacture is apparently a bigger source of doubt to the private sector than a similar process. Situations, such as proceeding from one process to the next or where machinery and plant are part of the building, do not always yield clear-cut answers. Possible solution for increasing the clarity of a process of manufacture or a similar process include, amongst others, clear guidelines which should be Issued by the Receiver of Revenue as well as a list of examples of processes of manufacture which are acceptable to the Receiver of Revenue.
Keywords: 650